Avaliação in vitro da potencial atividade antiviral de extratos de diferentes espécies de Annonaceae - Morales, Rafael Laurindo (2019)
Viruses are considered pathogens of great clinical importance to humans because of the various diseases that can cause, the Herpes Simplex virus type 1 (HSV-1), for example, are associated with orofacial and genital lesions, while arboviruses such as dengue viruses (DENV) and mayaro (MAYV) are related to febrile diseases, which may progress to more severe cases. Natural products, mainly plant derivatives, are considered promising sources of new compounds that can be used by the pharmaceutical industry to develop new drugs, including antivirals. Chemical and pharmacological studies of Annonaceae have shown accumulation secondary metabolites with important pharmacological activities, such as antiviral. This work aimed to evaluate the antivirals activities against HSV-1 (strain KOS) and against DENV-1 and MAYV viruses isolated from clinical samples, of n-hexane, ethyl acetate and methanolic extracts from leaves and branches of Fusaea longifolia Aubl. Saff., Guatteria punctata (Aubl.) R.A.Howard., Xylopia benthamii R.E.Fr., Duguetia sp and Xylopia (cf) frutescens, whose n-hexane extracts, ethyl acetate and methanolic extracts flowers were also evaluated; evaluate the antiviral effect of subfractions source ethyl acetate extract of the branches of F. longifolia (RAE) and of formulations whose extract was incorporated. The RAE extract was incorporated in the lipid core polymeric nanocapsule (LNC), in the positively charged LNC nanocapsule formulated with Eudragit RL polymer (LNC+ ), employing the interfacial deposition of preformed polymers, and in the liposome (LP), through reverse phase evaporation. The evaluation of antiviral activity was performed by the MTT assay, using concentrations below the Cytotoxic Concentration 50 %(CC50) previously determined by cytotoxicity evaluation, against Vero E6 cells, through the same assay. White nanostructures were used to eliminate interference from nanocarriers and aciclovir (15μM) as a positive control. The Effective Concentration 50 % (EC50) and selectivity index (IS = CC50 / EC50) were calculated for those materials that inhibited more than 50% of viral replication. All extracts were ineffective against DENV-1 and MAYV. The extracts GFAE, XfFM, XfRM, XfFlM, FAE and RAE were considered promising with a IS = 14.73; 7.41; 15.05; 16,70; 14.28 and 10.63, respectively. Xylopia benthamii and Duguetia sp. extracts weren't considered promising because they presented IS <5. Only F5 subfract presented antiviral potential with CC50> 1000 μg.mL-1; an EC 50 = 63.78 ± 2.73 and IS = 15.97. F5 subfract was 47.41% more selective than RAE. UPLC-MS/MS chromatographic analyzes of the RAE and F5 subfract revealed the presence of quercetin-3-β-D-glucoside; taxifolin; quercetin and luteolin in RAE and quercetin-3-β-D-glucoside in the F5 subfract. RAE presented virucidal effect and was efficient in posttreatment, with IS = 8.35 and 3.38, respectively. Of the nanosystems evaluated, only the LNC+ nanocapsules potentiated the effect of RAE, whereas when incorporated in LP it was not able to inhibit the replication of HSV-1. Among the species of Annonaceae studied, only Fusaea longifolia presented the most promising antiviral activity. New studies will be carried out to evaluate in which stages of the replication cycle of HSV-1 the RAE, F5 and LNC+ samples act.